The Editorial Board is Changing - LE Nicolle (Canadian Journal of Infectious Diseases and Medical Microbiology)
The success of The Canadian Journal of Infectious Diseases & Medical Microbiology over the past 16 years is largely attributable to the continuing and substantial support from a dedicated and enthusiastic Editorial Board. The individuals who have participated are listed on the masthead in each issue of the Journal. Many of the current Editorial Board members have participated continually since the initiation of the Journal - a commitment of over 16 years. They have provided oversight as the Journal has evolved, and their critical insights in the discussion of issues as they have developed, as well as their suggestions for new directions, have significantly contributed to the maintenance of Journal quality. Our associate editors have been particularly active. They have coordinated and, frequently, developed much of the content for the special sections - adult and paediatric infectious disease notes, clinical vignettes and reviews. They have also facilitated the peer review of submitted manuscripts by identifying reviewers and making recommendations for revisions and publication. These contributions have been essential to the continuing operation and high, scientific quality of the Journal.